2018
DOI: 10.7759/cureus.2235
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Incidence and Risk Reduction in the Hispanic Population

Abstract: Breast cancer is the most common non-skin cancer amongst women worldwide and is the fifth leading cause of cancer-related mortality overall. It is also the foremost reason for cancer-related mortality in Hispanic females in the United States (US). Although the current incidence of breast cancer is significantly lower in Hispanics compared to that of non-Hispanic Whites (NHW) and Blacks, (91.9, 128.1, and 124.3 per 100,000, respectively, annually), this may increase if Hispanics develop similar lifestyle behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…One in eight women in the USA will be diagnosed with breast cancer over the period of her life. It allocates 23% of the cancer cases and 14% of the cancer deaths worldwide (Power et al, 2018). Researches have showed that among breast cancer survivors the women with healthy life style and a diet high in fruits and vegetables, dietary fiber and low saturated fat, the risk of recurrence reduced by 31% (Duncan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One in eight women in the USA will be diagnosed with breast cancer over the period of her life. It allocates 23% of the cancer cases and 14% of the cancer deaths worldwide (Power et al, 2018). Researches have showed that among breast cancer survivors the women with healthy life style and a diet high in fruits and vegetables, dietary fiber and low saturated fat, the risk of recurrence reduced by 31% (Duncan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is one of the most common and leading causes of cancer death among women worldwide (Power et al, 2018). Early diagnosis of breast cancer can provide patients a wider range of therapeutic options as well as a higher success rate of therapy that lowers mortality.…”
Section: ) Introductionmentioning
confidence: 99%
“…Breast cancer is the most common cancer and considered to be second leading cause of death in United States. [1][2][3][4] Cytokine IL-6 is a proproliferative, anti-apoptotic, pleiotropic biochemical marker which play an important role in the immune regulation, ontogenesis and inflammatory change caused by surgical trauma and stress. 5,6,7 Blockade or modulation of the IL-6 signal manifest clinically as diseases, including inflammation-associated malignancies is well on its way in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Type of anesthesia used during these surgeries may augment these responses. 2,3 General anesthesia (GA) is by far the most common utility used for breast surgeries. Regional anesthesia has the advantage of preventing noxious stimuli from reaching the central nervous system and therefore can attenuate the surgical stress response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation